Deep Infiltrating Endometriosis: Making the Diagnosis. (November 2019) - Levine, Elliot M.; Fernandez, Carlos M.; Pham, Maggie; Shashoua, Abraham; Locher, Stephen
A case is described of a patient who presented with signs and symptoms suggestive of endometriosis. She underwent a diagnostic laparoscopy, which failed to identify any features of endometriosis. The patient subsequently underwent a 3D transvaginal sonogram that demonstrated evidence of a deep infiltrating endometriosis, affecting the right uterosacral ligament. This case demonstrates the diagnostic ability of 3D transvaginal sonography and, at the same time, the potential deficiency of laparoscopy to make the diagnosis of deep infiltrating endometriosis.